Functions of BCL-XL at the Interface between Cell Death and Metabolism - Judith Michels; Oliver Kepp; Laura Senovilla; Delphine Lissa; Maria Castedo; Guido Kroemer; Lorenzo Galluzzi (International Journal of Cell Biology)
The BCL-2 homolog BCL-XL, one of the two protein products of BCL2L1, has originally been characterized for its prominent prosurvival functions. Similar to BCL-2, BCL-XL binds to its multidomain proapoptotic counterparts BAX and BAK, hence preventing the formation of lethal pores in the mitochondrial outer membrane, as well as to multiple BH3-only proteins, thus interrupting apical proapoptotic signals. In addition, BCL-XL has been suggested to exert cytoprotective functions by sequestering a cytosolic pool of the pro-apoptotic transcription factor p53 and by binding to the voltage-dependent anion channel 1 (VDAC1), thereby inhibiting the so-called mitochondrial permeability transition (MPT). Thus, BCL-XL appears to play a prominent role in the regulation of multiple distinct types of cell death, including apoptosis and regulated necrosis. More recently, great attention has been given to the cell death-unrelated functions of BCL-2-like proteins. In particular, BCL-XL has been shown to modulate a number of pathophysiological processes, including—but not limited to—mitochondrial ATP synthesis, protein acetylation, autophagy and mitosis. In this short review article, we will discuss the functions of BCL-XL at the interface between cell death and metabolism.